PTSD REMISSION AFTER PROLONGED EXPOSURE TREATMENT IS ASSOCIATED WITH ANTERIOR CINGULATE CORTEX THINNING AND VOLUME REDUCTION. Issue 5 (10th February 2016) - Helpman, Liat; Papini, Santiago; Chhetry, Binod T.; Shvil, Erel; Rubin, Mikael; Sullivan, Gregory M.; Markowitz, John C.; Mann, J. John; Neria, Yuval
Abstract : Background: Brain structures underlying posttraumatic stress disorder (PTSD) have been a focus of imaging studies, but associations between treatment outcome and alterations in brain structures remain largely unexamined. We longitudinally examined the relation of structural changes in the rostral anterior cingulate cortex (rACC), a previously identified key region in the PTSD fear network, to outcome of prolonged exposure (PE) treatment. Method: The sample included 78 adults (53 women): 41 patients with PTSD and 37 trauma‐exposed healthy volunteers (TE‐HCs). Patients underwent a 10‐week course of PE treatment and completed pre‐ and posttreatment assessments and magnetic resonance imaging (MRI) structural scans. TE‐HCs also underwent assessment and MRI at baseline and 10 weeks later. PE remitters ( n  = 11), nonremitters ( n  = 14), and TE‐HCs, were compared at baseline on demographic and clinical characteristics and ACC structure. Remitters, nonremitters, and TE‐HCs were compared for pre‐ to posttreatment clinical and structural ACC change, controlling for potential confounding variables. Results: There were no baseline differences in structure between PTSD and TE‐HCs or remitters and nonremitters. Following treatment, PTSD remitters exhibited cortical thinning and volume decrease in the left rACC compared with PTSD nonremitters and TE‐HCs. Conclusions: These results, while in need of replication, suggest that PE treatment for PTSD, by extinguishing maladaptive trauma associations, may promote synaptic plasticity and structure change in rACC. Future research should explore possible underlying mechanisms.